Avaliação da composição e relativa eficácia de cinco cosméticos caseiros capilares veiculados na internet - (:unkn) unknown (ICET - Instituto de Ciências Exatas e Tecnologia (Itacoatiara), 2024)
Homemade hair care recipes are very popular on social media. With easy access to information and the search for natural solutions, many people turn to blogs, YouTube videos, social networks and other online platforms in search of these recipes to take care of their hair. However, this trend brings with it a number of risks and challenges. The dissemination of homemade hair recipes on social media can be problematic due to a lack of regulation, quality control and scientific validation. Many of these recipes are based on natural ingredients, such as essential oils, herbs and other products found at home, which can seem like an attractive alternative to commercial products. Based on this, the purpose of this study was to examine how effective five of the recipes posted on YouTube are, considering the relationship between their composition and hair physiology, clarify the selected components and gather reliable and scientific information on the use of natural products in hair care. Google Scholar, Pubmed, Research Gate, Science Direct and Scielo were used for the literature review. By analyzing 15 selected scientific articles, it was possible to extract substantial evidence indicating beneficial activities such as stimulating hair growth, reducing oiliness, preventing hair loss, improving shine and antimicrobial activity, attributed to the inputs previously mentioned in videos, namely onion, coffee, rice and guava leaf, in the context of hair physiology. The existing studies on the plant inputs mentioned, although numerous, are conducted predominantly in countries other than Brazil. The variation in the chemical components of plants from different countries, coupled with the differences between the extraction liquids, such as water, used to produce the extracts at home and in the laboratory, raises doubts about the real effectiveness of the shared recipes. This highlights the need for research carried out by Brazilian specialists to validate the biological activities cited in these homemade practices. In addition, it is important to emphasize the lack of scientific evidence supporting the efficacy of using olive oil and margarine as hair straightening agents, highlighting the importance of relying on information backed by scientific research when exploring beauty practices shared on social media.
Evaluation of the composition and relative efficacy of five homemade hair cosmetics advertised on the internet
Keywords: Receitas caseiras; Mídias sociais; Disseminação de receitas; Produtos naturais; CIÊNCIAS DA SAÚDE: FARMÁCIA; Cosméticos - Fórmulas e receitas; Produtos naturais - Fórmulas e receitas